The Influence of Direct Elections on Public Pragmatism in North Sulawesi Indonesia - B. Kairupan, Sisca; Javier C. Tuerah, Ignatius; H. E. Sendouw, Recky (International Journal of Engineering and Technology, 2018)
Democracy through direct election in the local elections is currently being implemented in Indonesia. The realization of democracy is basically an effort to empower the role and participation of society related manifestation of their political and social rights which are constitutionally guaranteed. The medium of democracy and democratization through political participation mechanism is expected to be able to provide multiple effects are not only related to the increasing size of the public maturation level to the rights and obligations of political constitution, but also the mechanism and system of direct election. Bargaining position of the society to determine a better future should be a necessary. Ironically, to give a reaction to the promises of the candidates, the community also expects the benefits which are realized in the form of short-term participation which await a clear material reward. As long as the candidates give the money, they will participate in the campaign and after which the wait to see if another candidate will give them money as well. The attitude of pragmatism has become irony in the spirit of democracy in achieving the real purpose. Pragmatism ultimately becomes destructive and leads to its adherent to be inconsistent. By making us of quantitative method this research would like to see the relationship between direct election and public pragmatism. The result showed that the relationship between the direct election and public pragmatism is moderate, however the both of the variables showed significant value and linear. This confirms that any increase in direct election variables will increase the public pragmatism.Â Â